Musk Ketone Induces Neural Stem Cell Proliferation and Differentiation in Cerebral Ischemia via Activation of the PI3K/Akt Signaling Pathway. (21st May 2020) - Zhou, Zheyi; Dun, Linglu; Wei, Bingxin; Gan, Yanyan; Liao, Zhongling; Lin, Xiumiao; Lu, Junlei; Liu, Guocheng; Xu, Hong; Lu, Changjun; An, Hongwei
Highlights: The role of musk ketone in cerebral ischemia is investigated. NSC proliferation and differentiation reduces cerebral ischemic injury. Musk ketone promotes NSC proliferation and differentiation. Musk ketone is neuroprotective in cerebral ischemia injury via PI3K/Akt activation. This study provides a novel therapeutic target for the treatment of cerebral ischemia. Abstract: Traditional Chinese medicine has been reported to influence the proliferation and differentiation of neural stem cells (NSCs) that may be protective against nervous system diseases. Recent evidence indicates the importance of musk ketone in nerve recovery and preventing secondary damage after cerebral ischemic injury. A middle cerebral artery occlusion (MCAO) rat model was established by a transient filament model, and rats were treated with musk ketone (0.9 or 1.8 μM). Next, an in vitro oxygen-glucose deprivation (OGD) cell model was established to study the effect of musk ketone on the proliferation and differentiation of NSCs. To determine the potential mechanisms of musk ketone involved in activities of NSCs, the effect of musk ketone on the PI3K/Akt signaling pathway activation was assessed. Furthermore, NSCs were treated with musk ketone in the presence of PI3K/Akt inhibitor Akti-1/2 to examine their roles on NSC proliferation and differentiation. Musk ketone reduced cerebral ischemic injury in a dose-dependent manner in rats. In addition, NSCs treated with musk ketone showed enhanced proliferation and differentiation along with increased PI3K/Akt signaling pathway activation. The effects of muck ketone were reversed by Akti-1/2. Altogether, musk ketone promoted NSC proliferation and differentiation and protected against cerebral ischemia by activating the PI3K/Akt signaling pathway, highlighting the potential of musk ketone as a physiologically validated approach for the treatment of cerebral ischemia.